2021
DOI: 10.1186/s12864-021-07709-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual species dynamic transcripts reveal the interaction mechanisms between Chrysanthemum morifolium and Alternaria alternata

Abstract: Background Chrysanthemum (Chrysanthemum morifolium) black spot disease caused by Alternaria alternata is one of the plant’s most destructive diseases. Dual RNA-seq was performed to simultaneously assess their transcriptomes to analyze the potential interaction mechanism between the two species, i.e., host and pathogen. Results C. morifolium and A. alternata were subjected to dual RNA-seq at 1, 12, and 24 h after inoculation, and differential expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Previously, only a few studies have been published on leaf blight disease caused by A. alternata on chrysanthemum. This includes a study in Prayagraj, India [ 36 ], Nanjing, China [ 12 , 21 ], and Greater Cairo, Egypt [ 35 ], the latter using seven cultivars (where ‘Dayangju’, ‘Jinba’, and ‘Chrystal Fresh White’ were among them. In the current study, the histological studies in the cross sections in both leaves and stems showed the highest values of cuticle thickness, cortex thickness, stem diameter, xylem vessel diameter, thickness of leaf epidermis, as well as lamina thickness in ‘Podolsk Purple’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, only a few studies have been published on leaf blight disease caused by A. alternata on chrysanthemum. This includes a study in Prayagraj, India [ 36 ], Nanjing, China [ 12 , 21 ], and Greater Cairo, Egypt [ 35 ], the latter using seven cultivars (where ‘Dayangju’, ‘Jinba’, and ‘Chrystal Fresh White’ were among them. In the current study, the histological studies in the cross sections in both leaves and stems showed the highest values of cuticle thickness, cortex thickness, stem diameter, xylem vessel diameter, thickness of leaf epidermis, as well as lamina thickness in ‘Podolsk Purple’.…”
Section: Discussionmentioning
confidence: 99%
“…can be destructive, causing black spot or leaf blight disease [ 9 ]. Leaf blight disease has severe impacts on chrysanthemum, which results in invaded Alternaria alternata that attacks mature leaves, with a rapid spread through plant tissues, soil, and surrounding air, especially under high temperature conditions [ 21 ]. A. alternata can cause serious damage after infection by secreting fungus toxins and enzymes for cell wall degrading in chrysanthemum tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The rooted seedlings were cultured in a 3:1 vermiculite mixture. Seedlings were grown in long-day conditions (16 hours of light, 25℃, relative humidity 75%) (Liu et al, 2021;Liu et al, 2020). Plants with uniform growth were randomly divided into two groups (n = 15): the control group and the treatment group.…”
Section: Plant Materials and Inoculation Treatmentmentioning
confidence: 99%
“…Using transcriptomic analysis, we reported that A. alternata activates the transcription of JA biosynthesis and signaling genes in chrysanthemum [ 31 ]. However, the molecular mechanism associated with JA-induced defense responses against A. alternata in chrysanthemum is largely unknown.…”
Section: Introductionmentioning
confidence: 99%